FUNDING AND LEVEL OF REIMBURSEMENT OF EXPENSE INCURRED ON STARTING AGROTOURISM ACTIVITY IN LUBLIN PROVINCE - Zawadka, Jan (Acta Scientiarum Polonorum. Oeconomia, 2010)
The aim of the paper was to show funding sources, amount and level of reimbursement of expenses incurred to launch projects related to rural tourism services. The study was conducted among 60 owners of agritourism farms providing their services in Lublin region. Diagnostic survey was used as a method. The studies show that the dominant motive of running agritourism is desire for obtaining an additional income. Owner’s expenses related to the start of this activity cover most of his savings. They are relatively small – at 80% of cases below 20 thousand PLN, but on their reimbursement takes place at least 2–3 years.